Effective Multifunctional Additive Engineering for Efficient and Stable Inverted Perovskite Solar Cells. Issue 11 (20th September 2022) - Li, Fuqiang; Huang, Xiaofeng; Xue, Junpeng; Liu, Fengwu; Kim, Danbi; Yang, Hyun-Seock; Yang, Eunhye; Shin, Insoo; Kim, Junghwan; Lee, Bo Ram; Park, Sung Heum
Abstract : Fabricating high‐quality perovskite films with large grain sizes and low‐defect densities is critical for developing efficient and stable perovskite solar cells (PeSCs). Herein, a simple and effective multifunctional additive engineering strategy is reported for producing high‐quality perovskite films. By including 2‐hexyl‐thiophene (2HT) with a thiophene electron‐pair donor and a long hydrophobic alkyl chain as an additive in the perovskite precursor solution, a perovskite film with high crystallinity, decreased trap density, and hindered ion migration is successfully obtained. These features are attributed to the strong coordinative interaction between the sulfur atom in 2HT and Pb 2+ in the perovskite film. The long alkyl chain of the 2HT additive assisted the production of a superior perovskite film with enlarged grain size, smooth surface topography, and hydrophobicity. Consequently, improved efficiency and prolonged operational stability are realized simultaneously for an inverted MAPbI3 PeSC with the 2HT additive. The device with 2HT delivers a higher power conversion efficiency of 20.61% compared with that of the control device (18.65%) and exhibits negligible hysteresis. Moreover, the stability of the device with the 2HT additive is superior to that of the control device under various testing conditions. Abstract : A multifunctional ligand, namely 2‐hexyl‐thiophene (2HT), is employed as an efficient additive. The addition of 2HT results in improved crystal growth, longer carrier lifetime, lower defect density, and thus improved film quality and stability. The device with 2HT provides an enhanced power conversion efficiency (PCE) of 20.61% and more environmental stability than that of the pristine device (PCE = 18.65%).